2017
DOI: 10.1007/s10815-017-1009-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection between day 3 and day 5/6 PGD embryos in couples with reciprocal or Robertsonian translocations

Abstract: This data demonstrates an increase in the proportion of genetically normal/balanced embryos at day 5/6 of development. This suggests a strong natural selection process between day 3 and day 5/6 in favour of normal/balanced embryos. These findings support performing PGD testing on day 5/6 of embryo development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
4
15
0
3
Order By: Relevance
“…These results correlate with Beyer et al, 2017 who reported an increase in the percentage of normal embryos between D3 embryos (22.3%) and D5 embryos (53.1%). 75 These results are also in agreement with Michal Dekel-Naftali et al 2013 who reported that while on ‘Day 3ʹ only 31% of the embryos were detected as normal, on ‘Day 5–6ʹ, 44% of the embryos were classified as normal. 76 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results correlate with Beyer et al, 2017 who reported an increase in the percentage of normal embryos between D3 embryos (22.3%) and D5 embryos (53.1%). 75 These results are also in agreement with Michal Dekel-Naftali et al 2013 who reported that while on ‘Day 3ʹ only 31% of the embryos were detected as normal, on ‘Day 5–6ʹ, 44% of the embryos were classified as normal. 76 …”
Section: Discussionsupporting
confidence: 88%
“…These results correlate with Beyer et al, 2017 who reported an increase in the percentage of normal embryos between D3 embryos (22.3%) and D5 embryos (53.1%). 75 These results are also in agreement with Michal Dekel-Naftali et al 2013 who reported that while on 'Day 3ʹ only 31% of the embryos were detected as normal, on 'Day 5-6ʹ, 44% of the embryos were classified as normal. 76 These findings confirm the results of Fragouli et al, 2013 and McCoy et al, 2015 that documented a strong natural selection process against chromosomal abnormalities during early embryogenesis, occurring specifically between day 3 and day 5/6 of development and is presumably due to impaired viability.…”
Section: Dovepresssupporting
confidence: 89%
“…Previous studies have aimed to characterize the type and frequency of the various modes of segregation observed through PGT from known translocation carriers (9,(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Based on the analysis of embryos from carrier parents, the number of unbalanced karyotypes declines rapidly from 3 to 5/6 days. 33,34 By the time that prenatal diagnosis is performed (late first trimester or second trimester), the risk for UPD when a fetus has a non-homologous Robertsonian translocation appears to be only 0.6%, or less. 35,36 These data are therefore also consistent with the early elimination of unbalanced karyotypes though mechanisms that are not substantially driven by rescue and generation of high numbers of UPDs.…”
Section: Discussionmentioning
confidence: 99%